Comportamento Planejado, Comportamento Passado e Familiaridade: Análise de Eficiência destes Preditores na Intenção de Ir à Vesperata de Diamantina-MG, Brasil / Theory of Planned Behavior, Past Behavior and Familiarity: Analysis of the Efficiency of these Predictors in the Intention to Visit Diamantina-MG Vesperata, Brazil - Araújo, Cristiane Gontijo; Tolentino, Isabela Gontijo (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2021)
RESUMO O turismo é um importante setor econômico. Entender a intenção de viagem das pessoas pode ser útil para o planejamento dos destinos, no atendimento à demanda da melhor forma possível. Nesse sentido, este estudo tem como objetivo avaliar o que influenciaria a intenção de ir à Vesperata de Diamantina, no Estado de Minas Gerais, utilizando para tal a Teoria do Comportamento Planejado, com a inclusão dos construtos comportamento passado e familiaridade. Para tanto, foi realizada pesquisa bibliográfica para elaboração de questionário, seguida de pesquisa quantitativa com 125 respondentes, sendo 101 válidos. Os resultados encontrados demonstraram relevância na inclusão dos novos construtos, que apresentaram efeito positivo na intenção de ir ao evento. Por outro lado, a atitude e a norma subjetiva, não apresentaram efeitos significativos na intenção, corroborando com estudos que tratam da complexidade da escolha de um destino turístico e da dificuldade de previsão da intenção, como em outros comportamentos mais comuns. PALAVRAS-CHAVE Turismo; Teoria do Comportamento Planejado; Comportamento Passado; Familiaridade; Vesperata de Diamantina, Minas Gerais, Brasil. ABSTRACT Tourism is an important economic sector. Understanding people's travel intentions can be useful for planning destinations, meeting demand as well as possible. In this sense, this study aims to assess what would influence the intention to go to the Diamantina Vesperata, in the State of Minas Gerais [Brazil], using the Theory of Planned Behavior for this purpose, with the inclusion of the constructs past behavior and familiarity. The methodology included bibliographic research for questionnaire elaboration, followed by quantitative research with 125 respondents, 101 of which are valid. The results showed relevance in the inclusion of the new constructs, which had a positive effect on the intention to attend the event. On the other hand, the attitude and the subjective norm did not present significant effects on the intention, corroborating with studies that deal with the complexity of the choice of tourist destination and the difficulty of forecasting the intention, as in other more common behaviors. KEYWORDS Tourism; Theory of Planned Behavior; Familiarity; Past Behavior; Diamantina Vesperata, Minbas Gerais, Brazil. AUTORIA Cristiane Gontijo Araújo - Mestranda na Universidade Federal de Minas Gerais, Belo Horizonte, Minas Gerais, Brasil. Currículo: http://orcid.org/0000-0003-2651-5187 E-mail: crisssgontijo@gmail.com Isabela Gontijo Tolentino - Mestranda na Universidade Federal de Minas Gerais, Belo Horizonte, Minas Gerais, Brasil. Currículo: http://orcid.org/0000-0002-1908-1686 E-mail: isabelagtolentino@gmail.com REFERÊNCIAS Ajzen, I. (1991). The theory of planned behavior. Organizational Behaviour and Human Decision Processes, 50(2), 179-211. Link Ajzen, I., & Fishbein, M. (1980). Understanding Attitudes and Predicting Social Behavior. New Jersey: Prentice-Hall. Alves, M. C., & Nascimento, A. F. (2014). Controvérsias analíticas sobre a turistificação da musicalidade diamantinense: o caso das Vesperatas. Cenário - Revista Interdisciplinar em Turismo e Território, 2(2), 123-139. Link Al Ziadat, M. T. (2014). Application of planned behavior theory in Jordanian tourism. International Journal of Marketing Studies, 6(2), 105-116. Link Bentler, P. M., & Speckart, G. (1979). Models of attitude-behavior relations. Psychological Review, 86(5), 452-464. Link Bianchi, C., Milberg, S., & Cuneo, A. (2017). Understanding travelers' intentions to visit a short versus long-haul emerging vacation destination: the case of Chile. Tourism Management, 59, 312-324. Link Chien, G. C. L., Yen, I. Y., & Hoang, P-Q. (2012). Combination of theory of planned behaviour and motivation: an exploratory study of potential beach-based resorts in Vietnam. Asia Pacific Journal of Tourism Research, 17(5), 489-508. Link Diehl, A. A., & Tatim, D. C. (2004). Pesquisa em Ciências Sociais Aplicadas: métodos e técnicas. São Paulo: Prentice Hall. Fishbein, M., & Ajzen, I. (1975). Belief, Attitude, Intention, and Behavior: an introduction to the theory and research. Massachusetts: Addison-Wesley. Fornell, C., & Larcker, D. F. (1981). Evaluating structural equation models with unobservable variables and measurement error. Journal of Marketing Research, 18(1), 39-50. Link Fredricks, A. J., & Dossett, D. L. (1983). Attitude-behavior relations: A comparison of the Fishbein-Ajzen and the Bentler-Speckart models. Journal of Personality and Social Psychology, 45(3), 501-512. Link Fundação João Pinheiro. (2017). Economia do Turismo de Minas Gerais: 2010 a 2014. Estatísticas & Informações: Indicadores Econômicos. Belo Horizonte: Fundação João Pinheiro. Gonçalvez, C. C. S., & Castellane, L. (2018). Determinantes do valor adicionado do turismo de Minas Gerais: uma análise com modelos de dados em painel. Marketing & Tourism Review, 3(1), 1-19. Link Guimarães, E. P., & Ferreira, W. R. (2006). Turismo de eventos e seus impactos: o caso da Vesperata em Diamantina - MG. Reuna, 11(3), 71-95. Link Hair Jr., J. F., Hult, T. M., Ringle, C. M. E., & Sarstedt, M. (2014). A Primer on Partial Least Squares Structural Equation Modeling (PLS-SEM). Los Angeles: Sage. Han, H., Lee, S., & Lee, C. K. (2011). Extending the theory of planned behaviour: visa exemptions and the traveller decision-making process. Tourism Geographies, 13(1), 45-74. Link Henseler, J., Ringle, C. M., & Sinkovics, R. R. (2009). The use of partial least squares path modeling in international marketing. Advances in International Marketing, 20, 277-319. Link Hsu, M-H., Yen, C-H., Chiu, C-M., & Chang, C-M. (2006). A longitudinal investigation of continued online shopping behavior: An extension of the theory of planned behavior. International Journal of Human-Computer Studies, 64(9), 889-904. Link Hsu, C. H. C., & Huang S. (2012). An extension of the theory of planned behavior model for tourists. Journal of Hospitality and Tourism Research, 36(3), 390-417. Link Hsu, M-C. (2013). The management of sports tourism: A causal modelling test of the theory of planned behaviour. International Journal of Management, 30(2), 474-496. Link Lam, T., & Hsu, C. H. C. (2006). Predicting behavioural intention of choosing a travel destination. Tourism Management, 27(4), 589-599. Link Lee, M., Han, H., & Lockyer, T. (2012). Attracting Japanese tourists for medical tourism experience. Journal of Travel & Tourism Marketing, 29(1), 69-86. Link Martin, D. S., Ramamonjiarivelo, Z., & Martin, W. S. (2011). Medtour: A scale for measuring medical tourism intentions. Tourism Review, 66(1/2), 45-56. Link Oliveira, R. A., Miranda, I. P., & Amaral, J. P. S. (2016). Gestão da Informação: o papel dos observatórios e turismo brasileiros para a tomada de decisão do setor público. Marketing & Tourism Review, 1(2), 1-31. Link Phetvaroon, K. (2006). Application of the theory of planned behaviour to select a destination after a crisis: a case study of Phuket, Thailand. Unpublished PhD Thesis, Oklahoma State University. Link Pires, M. C. (2017). Das viagens dos cientistas no século xix aos modernistas: a mineiridade e o despertar do turismo das cidades históricas de Minas Gerais, Brasil. Rosa dos Ventos – Turismo e Hospitalidade, 9(3), 405-416. Link Quintal, V. A., Lee, J. A., & Soutar, G. N. (2010). Risk, uncertainty, and the theory of planned behavior: a tourism example. Tourism Management, 31(6), 797-805. Link Roseta, P.; Sousa, B.B.; Roseta, L. (2020). Determiners in the consumer’s purchase decision process in ecotourism contexts: a Portuguese case study. Geosciences, 10(6), 1-18. Link Samara, B. S., & Barros, J. C. (2002). Pesquisa de Marketing – conceitos e metodologia. São Paulo: Prentice Hall. Shen, S., Schüttemeyer, A., & Braun, B. (2009). Visitors’intention to visit World Cultural Heritage sites: An empirical study of Suzhou, China. Journal of Travel & Tourism Marketing, 26(7), 722-734. Link Silva, D. R., & Sant’anna, P. A. (2015). Turismo e afirmação da identidade cultural: impactos psicossociais da atividade turística em Diamantina. Turismo - Visão e Ação, 17(1), 150-178. Link Silveira, C. E., & Medaglia, J. (2014). Perfil da demanda turística real de Diamantina e região: características de viagem, motivações, percepções & expectativas. Diamantina: UFVJM, 2014. Link Sousa, B., & Alves, G. (2019). The role of relationship marketing in behavioural intentions of medical tourism services and guest experiences. Journal of Hospitality and Tourism Insights, 2(3), 224-240. Link Sparks, B. A., & Pan, G. W. (2009). Chinese outbound tourists: unerstanding their attitudes, constraints and use of information sources. Tourism Management, 30(4), 483-494. Link World Travel & Tourism Council. (2019). Travel & Tourism Economic Impact 2019 World. Link Yang, J., Yuan, B., & Hu, P. (2009). Tourism destination image and visit intention: examining the role of familiarity. Journal of China Tourism Research, 5(2), 174-187. Link Yuzhanin, S., & Fisher, D. (2016). The efficacy of the theory of planned behavior for predicting intentions to choose a travel destination: a review. Tourism Review, 71(2), 135-147. Link PROCESSO EDITORIAL Recebido: 18 MAI 20; Aceito: 15 OUT 20.